Health literacy interventions for pregnant women with limited language proficiency in the country they live in: a systematic review - Marya Khan; Arti Dave; Madeleine Benton; Ngawai Moss; Mandeep Kaur Kaler (BMC Public Health)
Abstract Background Low health literacy can present significant risks throughout pregnancy, impacting both maternal and fetal health outcomes. Those who do not speak the main language of their country of residence are more likely to have lower health literacy. Considering the heightened challenges faced by this demographic in accessing, understanding, and engaging with health information and services, designing and implementing tailored interventions is crucial to mitigate health disparities. This review aims to identify and examine health literacy interventions developed for pregnant women whose first language differs from the language predominantly spoken in their residing country. Methods Electronic databases of Embase and Medline were searched using relevant search terms from their inception to July 2023. Data were extracted and analysed using narrative synthesis. Results Of the 1964 identified records, three were included. The studies were conducted in Australia and Denmark, and ranged in design, including: a cluster randomised controlled trial, mixed methods design; and qualitative design. Health literacy intervention modalities included midwifery education combined with a smartphone application and leaflet, culturally adapted group classes, and informative videos. The interventions were translated into various languages to cater to the target populations. Two studies used the Health Literacy Questionnaire to assess the intervention effectiveness, yielding contrasting results: one showed no improvement, while the other reported increased post-intervention health literacy scores. The third had not yet evaluated intervention effectiveness. Conclusions This review identifies a significant scarcity in health literacy interventions for pregnant women whose first language differs to the predominant language of the country they live in, despite their greater need for support. While few studies were found, their diversity suggests multiple strategies for enhancing health literacy. Bridging this health literacy gap for linguistically diverse pregnant populations could reduce disparities in maternal and fetal outcomes, underscoring the need for targeted, evaluated interventions that actively engage affected women and their support networks. Trial registration Registered with PROSPERO: CRD42023475511. Date of registration: 10.11.23.